2018
DOI: 10.1155/2018/9646937
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinium macrocarpon Aiton Extract Ameliorates Inflammation and Hyperalgesia through Oxidative Stress Inhibition in Experimental Acute Pancreatitis

Abstract: We evaluated the effect of the hydroethanolic extract of fruits of Vaccinium macrocarpon (HEVm) in a model of acute pancreatitis (AP) in mice. AP was induced by two injections of L-arginine and animals were treated with HEVm (50, 100, and 200 mg/kg, p.o.) or vehicle (saline) every 24 h, starting 1 h after the induction of AP. Phytochemical analysis of the extract and measurement of inflammatory and oxidative stress parameters, as well as abdominal hyperalgesia, were performed. Catechin, epicatechin, rutin, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…In the present study, Trolox was used as a positive control for both antioxidant assays, as the substance is considered to possess a very high antioxidant capacity; Trolox tends to exhibit a free radical scavenging activity that is up to eight times more effective than vitamin E [ 25 ]. Several studies have already confirmed the high antioxidant potential of large cranberry fruit extracts, and the results presented in this paper are consistent with the results reported previously in the literature [ 17 , 18 ]. After 18 months of storage under ambient conditions (temp.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, Trolox was used as a positive control for both antioxidant assays, as the substance is considered to possess a very high antioxidant capacity; Trolox tends to exhibit a free radical scavenging activity that is up to eight times more effective than vitamin E [ 25 ]. Several studies have already confirmed the high antioxidant potential of large cranberry fruit extracts, and the results presented in this paper are consistent with the results reported previously in the literature [ 17 , 18 ]. After 18 months of storage under ambient conditions (temp.…”
Section: Resultssupporting
confidence: 93%
“…Additionally, large cranberry fruit juice has been used to treat digestive tract disorders [ 11 ]. Moreover, large cranberry fruits and fruit extracts are considered a natural source of antioxidants [ 16 , 17 ] that reduce cellular oxidative stress and improve resistance to H 2 O 2 -induced DNA damage [ 18 ]. Cranberry fruit extracts are abundant in organic acids (i.e., malic, citric, quinic, and benzoic acids), saccharides (i.e., glucose and fructose), and phenolic compounds, which are considered the major compounds responsible for the therapeutic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic contents of IL-6, IL-1 , and TNF-, were decreased by the supplementation with cranberry. These results were confirmed in other experiment where found that cranberry reduced prostaglandin E2, IL-8, and IL-6, IL-8, generation in gingival fibroblasts stimulated with lipopolysaccharide in vitro assay 46 .In a model L-arginine-induced acute pancreatitis (AP) Vaccinium macrocarpon treatment reduce of AP-induced abdominal hyperalgesia as a consequence of the inhibition of pancreatic inflammatory cytokines, and block the stimulation of nociceptive pathways 47 . A secondary effect of pancreatitis is lung injury related to mortality in patients 48 In AP model lung MPO activity was significantly increased and cranberry treatment reduced MPO activity in lung as consequence of the reduction of pancreatic injury 49 .…”
Section: Neuroprotectionsupporting
confidence: 64%
“…41 Regular consumption of diets incorporating berries may thus reduce first-phase insulin secretion (mainly by decreasing carbohydrate absorption by inhibiting α-amylase and αglucosidase, and thereby glucose availability), 36,37 improve and preserve pancreatic β-cell function, principally via decreasing oxidative stress and inflammation that can be attributed to the function of anthocyanins. [42][43][44] In addition to the polyphenol content, whole berries are also a rich source of fiber that has been shown to delay gastric emptying and decrease glucose absorption that subsequently lead to decreases in postprandial rise of blood glucose. 45,46 In a Swedish study on the effects of a combination of berries, prebiotics and probiotics, a fermented oatmeal beverage was administered with vs. without bilberries or rosehip, and postprandial glucose and insulin levels were determined.…”
Section: Effects Of Berries On Glycemia and Insulin Resistance In Heamentioning
confidence: 99%